P PENERAPAN PROBIO 6 UNTUK MENINGKATKAN PRODUKSI IKAN AIR TAWAR DI POKDAKAN MINA HARAPAN JAYA, LAMPUNG TENGAH - Muliawati Handayani; Nuning Mahmudah Noor; Juli Nursandi (Universitas Negeri Surabaya, 2026)
The productivity of Nile tilapia farming at Mina Harapan Jaya group has shown room for improvement, prompting the integration of innovative technology to enhance efficiency and output. Engaging group members actively, the probiotic Probio 6 was incorporated into the fish growth cycle with comprehensive monitoring of the aquatic environment. The combination of theoretical learning and hands-on practice enhanced the members’ competence in probiotic-based aquaculture management. Throughout the maintenance period, the production cycle proceeded on schedule with low mortality rates and stable water quality. This technological application resulted in increased production and cost efficiency, ultimately contributing to improved income and welfare of the fish farmers